Tampilan reproduksi sapi perah pada berbagai paritas di wilayah KUD Batu - Achmad subhi Gumilar; Trinil Susilawati; Sri Wahyuningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2012)
The purpose of this study was to determine the performance of reproduction in dairy cattle, the views of service per conception, days open, and calving interval. The material used in this study is the implementation of recording data or artificial insemination in 100 dairy cows females have at least twice to parturition known calving interval. Samples were selected randomly within the same district in Batu. The method used in this research is a case study. The data is taken primary and secondary data. Primary data retrieval is done by direct observation (observation), which includes several variables, where the variables include: the identity of the breeder, the number of cattle, cages and feeding and drinking. As for the secondary data obtained by recording the card Artificial Insemination (AI) owned by farmers. Sampling was done by purposive sampling and random with the following conditions: sampling was done by purposive sampling with the following conditions: minimal yearling heifer parturition twice and had a complete recording AI, including, the date AI and the date of parturition. Results from this study is the performance of reproduction in the dairy cooperatives Batu showed unfavorable results, average - the average total value of S/C of parity 1 s / d 6 is, 1.93 ± 1.18. As for the average - the average total value of DO and CI parity 1 s / d 5 is, 171.70 ± 132.20 days and 450.92 ± 132.83 days. In addition, the assessment of S / C, DO and CI at different parity using statistical tests showed that the S / C, DO and CI at various parity was not significantly different (P> 0.05).It concluded that reproduction display AI results in the KUD BATU less than the maximum and the difference between parity does not affect the value of the S / C, DO, and CI.